SN Video coding and web development. - McDonnell, Kevin (SN Video Coding and Web Development, 2020)
This video introduces Cosmos DB and highlights the benefits that using Cosmos DB can bring to your applications and clients. Watching this video helps to increase your toolbox of knowledge around Azure and build your skills on this important cloud platform. Examples in the video are built in C#, the language from which Cosmos DB is most commonly used. A running example throughout the video demonstrates the basics of entering data, querying and updating data, deleting data, and working with the Cosmos DB change feed.